Book review “Median Archaeology” - Reza Mehrafarin (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Median age is of the most important historical periods of Iran because, during this period, Iranian / Aryan groups were able to form a government in the West of modern Iran for the first time. This government provided the context of the emergence and flourishing of the Achaemenid Empire and transferred many of the principles of governance, social, religious and civilizational foundations to another branch. Access to the information and documentation of this government are limited due to the lack of historical documentation sources, notably Iranian and archaeological evidence. These factors led to an inadequate access to publications from Median period to archaeologists and Median scholars. Thus, students of archeology relied heavily on the dispersed pamphlets that provided such incomplete and duplicated documents since the establishment of this academic field.Publication of “Median Archaeology” has largely filled this gap for this period and created opportunity for archeology students to study all the information related to the Syllabus of Median archaeology. The book has some advantages and shortcomings that we have enumerated them so as to improve the quality of the book in the subsequent editions.